2021
DOI: 10.3390/ma14164636
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Functions of Inorganic Chemical Binders for Refractories

Abstract: For refractory application, amongst others, inorganic chemical binders are used to shape and process loose, unpacked materials. The binder influences the chemical composition within the ceramic body during setting, aging and firing and thus the finally reached properties of the refractory material. For an effective design of tailored materials with required properties, the mode of action of the binder systems should carefully be investigated. A combination of both structure analysis techniques and macroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…27 These condensation reactions can occur at low temperatures (<500 • C) and result in an inorganic polymer with good mechanical toughness. 28 This inorganic polymer is an interesting low process temperature binder for higher sintering temperature oxide ceramic par-ticles. Prior work has shown an ability to thermally convert Al(H 2 PO 4 ) 3 into crystalline AIPO 4 to bind oxide ceramics such as silica and alumina 29,30 and form a monolithic ceramic.…”
Section: Background: Phosphate Bindersmentioning
confidence: 99%
See 2 more Smart Citations
“…27 These condensation reactions can occur at low temperatures (<500 • C) and result in an inorganic polymer with good mechanical toughness. 28 This inorganic polymer is an interesting low process temperature binder for higher sintering temperature oxide ceramic par-ticles. Prior work has shown an ability to thermally convert Al(H 2 PO 4 ) 3 into crystalline AIPO 4 to bind oxide ceramics such as silica and alumina 29,30 and form a monolithic ceramic.…”
Section: Background: Phosphate Bindersmentioning
confidence: 99%
“…28 This inorganic polymer is an interesting low process temperature binder for higher sintering temperature oxide ceramic par-ticles. Prior work has shown an ability to thermally convert Al(H 2 PO 4 ) 3 into crystalline AIPO 4 to bind oxide ceramics such as silica and alumina 29,30 and form a monolithic ceramic. 31 The adhesive ceramic binding mechanism of ADP occurs via condensation reactions between the hydroxyl groups of dihydrogen phosphate and the hydroxyl groups on the ceramic powder surface (Figure 1B).…”
Section: Background: Phosphate Bindersmentioning
confidence: 99%
See 1 more Smart Citation
“…Each type of binder has its own set of advantages and disadvantages. Among all the various binder types, phosphate binders are a well‐recognized class that is widely used in refractory applications 35 . Some research studies have also demonstrated that the use of sulfate, in combination with phosphate, has a relatively superior binding effect 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Among all the various binder types, phosphate binders are a well-recognized class that is widely used in refractory applications. 35 Some research studies have also demonstrated that the use of sulfate, in combination with phosphate, has a relatively superior binding effect. 36 However, the application of aluminum sulfate exclusively as a binding agent to form green, porous structures is yet to be reported.…”
mentioning
confidence: 99%